(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Medical emergencies can occur unexpectedly in various settings, including schools, where students are highly active. Equipping students with basic first aid skills is important for quick response and potentially life-saving assistance. This study assesses the basic first aid skills of senior high school students at Union Christian College, City of San Fernando, La Union. Quantitative approach through descriptive design was utilized. Employing a total enumeration approach, data was collected from 211 Grade 11 and 12 students using a survey questionnaire. Findings reveal a high exposure to wounds and a generally low exposure to other incidents, suggesting that injuries requiring wound treatment are more prevalent among them compared to other physical incidents. Also, the respondents have moderate competence when dealing with the different emergencies at school wherein they are more competent in wound treatment, while less competent in choking and hyperventilation. The weak positive correlation between exposure and competence suggests limited exposure hindering skill development. The type of community living in impact competence, with urban and rural residents demonstrating higher proficiency. The study emphasizes the importance of promoting health and safety education, particularly in wound treatment and emergency response, to mitigate the impact of injuries and improve overall well-being. This provided a baseline for designing a first aid video demonstration tailored to the needs of the students that is recommended for adoption as learning resource material.